Narrating the Nation: Identity, War, and Media Representation in Narayan Wagle’s Palpasa Café - Luitel, Peshal Kumar; Rai, Prakash (Academia Journal of Humanities & Social Sciences, 2026)
The paper examines Narayan Wagle’s Palpasa Cafe (2005) to explore the interaction and interplay between identity, conflict, and media representation during the Maoist insurgency that spanned from 1996 to 2006. Against this backdrop, the novel illustrates the fright, displacement, and ambiguity Nepali people experienced, constructing an alternative view towards the Nepali nation and nationalism. The study uses the qualitative methods, particularly the thematic and textual analysis methods to analyze the narrative structure, characters’ interaction, motifs and themes, and representational strategies through lived experiences and the mediated storytelling. The protagonists of the novel, Drishya and Palpasa represent two distinct but interconnected aspects of Nepali identity. As an artist, Drishya has profoundly been moved by the direct experiences of violence while Palpasa searches for meaning, identity, and belonging through a diasporic gaze in a war-torn homeland. The different but interrelated experiences of both characters show that a common national identity, built by more than just war, but shaped by cultural memory, moral duty, and personal grief. Thus, the study utilizes Anderson’s (1983) theory of “imagined communities,” Foucault’s (1977) notion of discourse, and Hall’s (1996) insights of identity to back up the research issue and support for textual analysis. In this way, the paper addresses a gap in current scholarship to enhance the comprehension of how Nepali war literature contributes to the construction and reconstruction of a national identity, during the harsh political upheaval.